2003
DOI: 10.3354/meps260173
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent diel vertical migration in northern krill Meganyctiphanes norvegica and its consequences for population dynamics

Abstract: The diel vertical migration (DVM) and population dynamics of northern krill were investigated in the Clyde Sea over several years using depth-discrete net-sampling and a moored 300 kHz acoustic Doppler current profiler. Krill performed DVM throughout each year of sampling. The respective arrival and departure of the krill scattering layer to and from the upper layers occurred consistently 30 min after sunset and 30 min before sunrise. DVM of males and females was different, with females migrating closer to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 36 publications
0
44
0
Order By: Relevance
“…We are confident that both sexes are the same age, since they were the same size as in the population study of Boysen and Buchholz (1984) and in the Clyde Sea study of Tarling (2003) when cohorts were followed over a complete annual cycle. This means that growth increments (GIs) at moult must be different between sexes.…”
Section: The Body Length Of Males and Femalesmentioning
confidence: 95%
See 1 more Smart Citation
“…We are confident that both sexes are the same age, since they were the same size as in the population study of Boysen and Buchholz (1984) and in the Clyde Sea study of Tarling (2003) when cohorts were followed over a complete annual cycle. This means that growth increments (GIs) at moult must be different between sexes.…”
Section: The Body Length Of Males and Femalesmentioning
confidence: 95%
“…It may be through this means that they obtain enough food to avoid the allocation conflict between growth and reproduction that could affect the relative growth rates of males and females in crustaceans (Hartnoll 1985;Conan 1985). However, high feeding rates are achieved at the cost of greater exposure to predation risk (Tarling 2003). This may explain why, as a rule, numbers of females are smaller than those of males.…”
Section: The Body Length Of Males and Femalesmentioning
confidence: 96%
“…In Antarctic krill, it was demonstrated that males grow faster but die younger than females (Kawaguchi et al 2007), and this pattern might also hold for tropical species under mixed column water conditions. Tarling (2003) mentioned that selective mortality, either through physiological differences between sexes or sex-specific predation, is the major factor responsible for the substantial sex ratio variability in Meganyctiphanes norvegica. Hill et al (1996) also found evidence that males of E. superba in the northwest of South Georgia evade nets and predators such as macaroni penguins Eudyptes chrysolophus more efficiently than females.…”
Section: Seasonal/interannual Variability Of Tropical Euphausiidsmentioning
confidence: 99%
“…Previous krill studies in the ETP have been realized from single oceanographic cruises (Brinton 1979, Färber-Lorda et al 1994, Gómez-Gutiérrez & Hernández-Trujillo 1994. Relatively more extensive studies about euphausiid biology and ecology have been performed on both sides of the Baja California peninsula (Brinton 1962, 1981, Brinton & Townsend 1980, 2003, Brinton et al 1986, Lavaniegos 1994). …”
Section: Introductionmentioning
confidence: 99%
“…Comparison between summer distribution of large whale species in the Gulf (solid white circles) from the only systematic survey made (1995 and 1996 aerial survey by Kingsley & Reeves 1998) and averaged simulated abundance of zooplankton during July and August 1997. Whale species comprise blue, fin, and humpback (see Kingsley & Reeves 1998 for more details) 1993, Buchholz et al 1995, Bergström & Strömberg 1997, Onsrud & Kaartvedt 1998, Pearre 2003, Tarling 2003. Although krill cross the thermocline (Simard et al 1986b), their particular location in relation to this boundary (and particularly the exact duration of their stay above it, where mean currents are stronger and outflowing) are not well known and have not been considered in any model.…”
Section: Sensitivity To Biological Parametersmentioning
confidence: 99%